2014
DOI: 10.1186/s13032-014-0021-y
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome and satisfaction with a “self-care” protocol for the management of mallet finger injuries: a case-series

Abstract: BackgroundMallet finger injuries are usually successfully treated non-operatively with a splint. Most patients are reviewed at least twice in a clinic after the initial presentation in A&E. A new protocol promoting “self-care” was introduced at our institution. Patients were provided with structured verbal and written information, and given access to a telephone helpline.MethodsA prospective electronic patient record was used to identify all patients who presented to the emergency department with a mallet fing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 12 publications
2
31
1
Order By: Relevance
“…Others commented that the fact they did not have to wait to be seen or park at the hospital made them prefer TFU. Levels of satisfaction are comparable to those in other studies assessing TFU (Gray et al, 2010;Brooksbank et al, 2014). The high levels of patient satisfaction add significant weight to the use of TFU in this setting.…”
Section: Discussionsupporting
confidence: 79%
“…Others commented that the fact they did not have to wait to be seen or park at the hospital made them prefer TFU. Levels of satisfaction are comparable to those in other studies assessing TFU (Gray et al, 2010;Brooksbank et al, 2014). The high levels of patient satisfaction add significant weight to the use of TFU in this setting.…”
Section: Discussionsupporting
confidence: 79%
“…To date, we have published evidence about the satisfaction and clinical outcome of radial head fractures and mallet finger injuries. 1 - 5 We have also previously demonstrated that the system resulted in improvements in the flow of patients in the Emergency Department (ED), with no adverse effects of providing more information at the first point of contact in order to reduce the number of follow-up visits. 5 This “balance” measure demonstrates that this redesigned pathway has not had a harmful effect on our linked units.…”
Section: Discussionmentioning
confidence: 99%
“…Our institution introduced a service redesign in 2010 that was primarily focused on improving the management of minor orthopaedic trauma. 1 - 5 The delivery of outpatient fracture care has not changed significantly since guidelines were set by the British Medical Association in 1935. 6 These historical guidelines were a response to wide variation and poor practice in the management of common injuries.…”
Section: Introductionmentioning
confidence: 99%
“…Reasons for non-adherence to medical guidance are multi-faceted, with socioeconomic, health-care systemrelated, condition-related, treatment-related, and patient-related factors all contributing [1]. With regard to orthosis use, specific factors such as discomfort, ill fit, inconvenience, skin irritation, and issues such as disturbed sleep have all been postulated as reasons for nonadherence [5][6][7][8]. Although not a straightforward relationship, there is evidence to support that adherence to the prescribed use of an orthosis in acute conditions leads to superior outcomes following muscle tears [9] and tendon injuries [10][11][12] and post-operatively [13].…”
Section: Introductionmentioning
confidence: 99%